Statistics, data mining, and machine learning in astronomy : a practical Python guide for the analysis of survey data - Ivezić, Željko (Array, 2014)
Sadržaj: 1. About the book and supporting material ; 2. Fast computation on massive data sets ; 3. Probability and statistical distributions ; 4. Classical statistical inference ; 5. Bayesian statistical inference ; 6. Searching for structure in point data ; 7. Dimensionality and its reduction ; 8. Regression and model fitting ; 9. Classification ; 10. Time series analysis